Stabilisasi Tanah Gambut Menggunakan Geopolimer Hybrid - Erwin Erwin; Gunawan Wibisono; Monita Olivia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peat soil has high moisture content and organic content. Peat soil is stabilized to improve soil properties and increase its strength. This study examines stabilization mixtures on peat soil with geopolymers hybrid. Geopolymers are alternative substitutes for cement, made from remnants of industrial waste which rich of silica and alumina, such as fly ash, husk ash, slag and palm ash. The geopolymer bond can be activated with an activator solution. Geopolymers were added by OPC to accelerate hardening and optimize strength on the ground. The purpose of this study is to compare the compressive strength of peat soil mixed with the soil geopolymer hybrid using an Unconfined Compressive Strength (UCS) Test. This study used a different variation of the treatment that are the age of 7 days and 28 days. Binder for the mixed set of 200 kg/m3 with geopolymer materials used by 50% of the binder and the OPC which was used by 50% and 100% of the binder. The results showed that the compressive strength with hybrid geopolymer mixture tends to increase from 7 days to 28 days and the compressive strength of geopolymer hybrid is higher than peat. Based on the results of this test it is concluded that peat soil using a mixture of hybrid geopolymer could increase the value of compressive strength.Keywords: peat soil, OPC, fly ash, geopolymer hybrid, UCS